Removal of Rhodamine-B from Aqueous Solution by Adsorption Using Water Hyacinth Ash - SWEETLIN RAJULA RUBAVATHI, D.; THEODORE DAVID, S.; BALAKUMAR, S. (Asian Journal of Chemistry, 2010)
The use of cheap and ecofriendly adsorbents have been studied as an alternative substitution of activated carbon for the removal of dyes from wastewater. Adsorbents prepared from water hyacinth ash are used to remove the rhodamine-B from aqueous solution. The effect of various experimental parameters has been investigated using a batch adsorption technique to obtain information on treating effluents from the dye industry. The extent of dye removal increased with decrease in the initial concentration of the dye and also increased with increase in contact time and amount of adsorbent. Adsorption data were modeled using the Freundlich adsorption isotherm and first order kinetic equation Lagergren equation.